Risk‐mitigating behaviours in people with inflammatory skin and joint disease during the COVID‐19 pandemic differ by treatment type: a cross‐sectional patient survey. (9th March 2021) - Mahil, S.K.; Yates, M.; Langan, S.M.; Yiu, Z.Z.N.; Tsakok, T.; Dand, N.; Mason, K.J.; McAteer, H.; Meynell, F.; Coker, B.; Vincent, A.; Urmston, D.; et al.
Summary: Background: Registry data suggest that people with immune‐mediated inflammatory diseases (IMIDs) receiving targeted systemic therapies have fewer adverse coronavirus disease 2019 (COVID‐19) outcomes compared with patients receiving no systemic treatments. Objectives: We used international patient survey data to explore the hypothesis that greater risk‐mitigating behaviour in those receiving targeted therapies may account, at least in part, for this observation. Methods: Online surveys were completed by individuals with psoriasis (globally) or rheumatic and musculoskeletal diseases (RMDs) (UK only) between 4 May and 7 September 2020. We used multiple logistic regression to assess the association between treatment type and risk‐mitigating behaviour, adjusting for clinical and demographic characteristics. We characterized international variation in a mixed‐effects model. Results: Of 3720 participants (2869 psoriasis, 851 RMDs) from 74 countries, 2262 (60·8%) reported the most stringent risk‐mitigating behaviour (classified here under the umbrella term 'shielding'). A greater proportion of those receiving targeted therapies (biologics and Janus Kinase inhibitors) reported shielding compared with those receiving no systemic therapy [adjusted odds ratio (OR) 1·63, 95% confidence interval (CI) 1·35–1·97]. The association between targeted therapy and shielding was preserved when standard systemic therapy was used as the reference group (OR 1·39, 95% CI 1·23–1·56). Shielding was associated with established risk factors for severe COVID‐19 [male sex (OR 1·14, 95% CI 1·05–1·24), obesity (OR 1·37, 95% CI 1·23–1·54), comorbidity burden (OR 1·43, 95% CI 1·15–1·78)], a primary indication of RMDs (OR 1·37, 95% CI 1·27–1·48) and a positive anxiety or depression screen (OR 1·57, 95% CI 1·36–1·80). Modest differences in the proportion shielding were observed across nations. Conclusions: Greater risk‐mitigating behaviour among people with IMIDs receiving targeted therapies may contribute to the reported lower risk of adverse COVID‐19 outcomes. The behaviour variation across treatment groups, IMIDs and nations reinforces the need for clear evidence‐based patient communication on risk‐mitigation strategies and may help inform updated public health guidelines as the pandemic continues. Abstract : What is already known about this topic? At the beginning of the coronavirus disease 2019 (COVID‐19) pandemic, patients with immune‐mediated inflammatory diseases (IMIDs) on targeted systemic therapies were considered to be at higher risk of severe COVID‐19. Subsequent clinician‐reported registry data suggest that targeted systemic therapy use is associated with fewer adverse COVID‐19 outcomes compared with no systemic therapy. What does this study add? We characterize shielding behaviour in 3720 patients with IMIDs from a global self‐report survey. Use of targeted systemic therapy associates with increased shielding behaviour, compared with standard systemics or no therapy, as do demographic risk factors for severe COVID‐19 including male sex and obesity. Greater risk‐mitigating behaviour among people with IMIDs receiving targeted therapies may contribute to the reported lower risk of adverse COVID‐19 outcomes. Behaviour variation across treatment groups reinforces the need for clear, evidence‐based patient communication on risk‐mitigation strategies. These data may help to inform updated public health guidelines as the pandemic continues. Linked Comment:  G. Becher and A.D. Burden. Br J Dermatol 2021; 185 :7–8 .